Falling Short on Long-Term Care Efficiency Change? A Non-Parametric Approach - Augusto Carlos Mercadier; Irene Belmonte-Martín; Lidia Ortiz (Economies)
The European Commission’s 2015 aging report forecasts a substantial increase in public spending on Long-Term Care (LTC) for OECD countries by 2060, posing significant fiscal challenges. This study aims to assess the efficiency and productivity of the LTC sector from 2010 to 2019 and explore whether efficiency gains can alleviate these fiscal pressures. Using a non-parametric Data Envelopment Analysis (DEA) model, combined with Tobit regression, we estimate the efficiency of OECD countries and examine the role of decentralization in shaping performance outcomes. The findings reveal that, on average, countries operate at 94% efficiency, with modest productivity growth. However, technical inefficiencies persist, especially in unitary countries, while federal countries, though initially less efficient, show greater improvements over time. Despite these gains, the current efficiency levels are insufficient to counterbalance the projected increase in LTC demand. Policymakers should prioritize reforms that enhance efficiency through decentralization, promoting accountability and competition as mechanisms to sustain the LTC system in the face of demographic shifts.